Analisis Gaya Kepemimpinan Demokratis Sebagai Upaya Optimalisasi Kinerja Karyawan - Debora Silvia Hutagalung; Eka Pratiwi Septania Parapat (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2020)
The purpose of this study was to find out how the Leadership Style at PT. Radio Swara Cendrawasih Karya Murni Pematang Siantar Leadership style talks about how a leader applies his leadership. Democratic leadership is the way a leader influences the behavior of his subordinates, in order to cooperate and work productively in order to achieve the goals of the organization. The leadership style of a leader in motivating his employees in carrying out his company's activities will greatly determine the performance of the company or organization. In the leader's relationship with his subordinates, a number of employees expect to get an open leader's treatment and provide flexibility in their work. The research method used is descriptive method with a qualitative approach by collecting data through interviews and observations. The results show that the leadership style at PT. Radio Swara Cendrawasih Karya Murni Pematangsiantar cannot be said to be democratic because a leader has not provided direction and input to his subordinates and also does not want to accept criticism from employees against the leadership and is not in accordance with the characteristics stated by Rivai. (2014) that democratic leadership is always trying to synchronize the interests and personal of subordinates, cooperation and teamwork, and also not in accordance with Ariani (2014) including decisions made together, respecting the potential of their subordinates, listening to criticism.